Sustainable well-being: An empirical exploration on human interdependence with the environment - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor; Abdullah, Alias (2016)
This study is a part of ongoing research to discover subjective measures of sustainable well-being manifested in (i) Human Interdependence with other Humans (HIH) and (ii) Human Interdependence with the Environment (HIE). This paper focuses on HIE. ISSUES: A growing number of studies on subjective well-being claimed that sustainable well-being is a result of human interdependency. However, there is a lack of conclusive study on dimensions and components that determine the human interdependence with the environment. AIM: This study intends to provide empirical evidence on the components that constitute HIE. METHOD: Questionnaire Survey and Principal Component Analysis (PCA) were adopted to determine the components of HIE. Before the Questionnaires, the research had already theoretically explored four separate dimensions to HIE. The dimensions of HIE were (i) personality and lifestyle, (ii) interaction with nature, (iii) environmental attitude and (iv) external condition to behaviour. Potential and measurable HIE indicators were discovered through literature review and converted into 40 self-reported items. Survey Questionnaires were conducted inquiring respondents of their levels of HIE. FINDINGS: There were 12 components extracted in total, based on four separate PCA analysis for each HIE dimension. LIMITATION: Full reliance on literature review and PCA in discovering the components for HIE is the weakness of the research. An in-depth qualitative approach such as semi-structured interviews could potentially determine other possible determinants to HIE. SIGNIFICANCE: This study identifies the determinants of HIE. The empirical evidence of HIE contributes to the practicality of measuring sustainable well-being through HIE at the local scale.